Pengembangan Media Pembelajaran Pendidikan Agama Islam Berbasis Komik pada Materi Perilaku Terpuji untuk Siswa Kelas VII Sekolah Menengah Pertama - Hamid, Abdul; Nursyamsi, Nursyamsi (Fakultas Tarbiyah dan Ilmu Keguruan, 2025)
This research aims to determine the analysis of the needs of Islamic religious education learning media based on comics, to determine the design of the development of comic-based learning media and to determine the validity and practicality of comic-based learning media developed in class VII of SMP Negeri 1 Rongkong. This research uses the Research and Development (R&D) type of research using the ADDIE model consisting of 5 stages, namely: (a) Analysis stage, (b) design stage, (c) development stage, (d) implementation stage, (e) evaluation stage. This research was conducted at SMP Negeri 1 Rongkong, North Luwu Regency. The subjects of this study were teachers and students of class VII of SMP Negeri 1 Rongkong with a total of 23 students who used the comic-based media that was developed. The object of this study is comic-based media. Data collection techniques used by researchers are observation, interviews, questionnaires and documentation. This research produced a learning media in the form of comics that have met the valid category of the results of the validity of comic media. Based on the results of the validity of comic media that have been validated with categories including material experts obtained value of 89% with a very valid category, media experts obtained a value of 72% with a valid category and language experts obtained a value of 93% with a very valid category. The results of student practicality based on trial responses with 23 students obtained a value of 96.28% with a very valid category while the results of teacher practicality obtained a value of 90.20% with a very practical category.